2021
DOI: 10.1007/s11116-021-10209-0
|View full text |Cite
|
Sign up to set email alerts
|

Do frequent satisfying trips by public transport impact its intended use in later life?

Abstract: Previous studies have indicated that factors such as the built environment, attitudes and past behaviour can influence travel behaviour. However, the possible effect of travel satisfaction on travel mode choice remains underexplored, despite many studies focusing on travel satisfaction over the past years. It is likely that individuals experiencing satisfying trips with a certain travel mode will use this mode (more) frequently for future trips. In this study—using data from 984 students from Laval University,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…In areas that have poor transit service and sprawled land use patterns, it is very difficult for other modes of transportation to compete effectively with the automobile. However, based on the findings in this study, mere investments in alternative modes of transportation and improving their level of service (as explored in Eriksson et al [ 8, 9 ] and De Vos et al [ 38 ]) are not necessarily going to draw people away from the automobile if the use of the auto-driving mode is itself associated with higher levels of satisfaction. This points to the continuing struggle of policymakers in creating effective alternatives to automobile driving and removing system constraints for switching to alternative modes of transportation ( 39 ).…”
Section: Study Implications and Conclusionmentioning
confidence: 72%
“…In areas that have poor transit service and sprawled land use patterns, it is very difficult for other modes of transportation to compete effectively with the automobile. However, based on the findings in this study, mere investments in alternative modes of transportation and improving their level of service (as explored in Eriksson et al [ 8, 9 ] and De Vos et al [ 38 ]) are not necessarily going to draw people away from the automobile if the use of the auto-driving mode is itself associated with higher levels of satisfaction. This points to the continuing struggle of policymakers in creating effective alternatives to automobile driving and removing system constraints for switching to alternative modes of transportation ( 39 ).…”
Section: Study Implications and Conclusionmentioning
confidence: 72%
“…In turn, this leads to further problems of poor comfort for the users and inefficient use of capacity for the operator. Overcrowding can affect satisfaction, which has been shown to affect intention to use public transport ( 2 ). Therefore, finding an efficient, economical, and environmental way to distribute passengers should improve customer satisfaction, reduce operating costs, and reduce resource consumption.…”
mentioning
confidence: 99%
“…The authors suggested that, in future research, the relationship between the desired PT frequency and the satisfaction level should be considered. It has also been proven that travel satisfaction plays a key role in shaping habitual PT use; for instance, by providing reliable and free PT [25]. Moreover, in the last ten years, researchers have investigated and assessed the relationship between travel satisfaction and trip characteristics [26], such as the mode choice and travel time [27,28], as well as how these factors correlate with the built environment [29].…”
Section: Literature Reviewmentioning
confidence: 99%